Studying The Effect of Age and Gender on The Distribution of The two types keratocystic odontogenic tumour - Kochaji, Nabil (Latakia University Journal -Medical Sciences Series, 2018)
Odontogenic tumors are lesions derived from the epithelial and/or mesenchymal elements of the tooth-forming apparatus and are therefore found within the jaw bone or soft tissue overlying teeth. These tooth development-associated tumors are generally benign, but several odontogenic tumors are capable of aggressive growth and locally invasive behavior with a high rate of recurrence. In this study we have studied the effect of patient age and gender on the distribution of keratocystic odontogenic tumour with its two types (prakeratinized and Orthokeratinized). we conclude that age and gender of patient can affect type of tumour Where the incidence of tumour was higher in males and was distributed between the third and fourth decades of life. دراسة تأثير العمر والجنس على توزع نمطي الورم الكيسي المتقرن سنيّ المنشأ الأورام سنيّة المنشأ هي آفات تنشأ من البشرة أو النسيج الضام المُشكلة للأسنان و لذلك توجد ضمن عظم الفك أو في النسج الرخوة المُغطية للأسنان. معظم هذه الأورام سليمة إلا أن عدد من هذه الأورام عندها قابلية للنمو العدواني و الغزو الموضعي مع معدل عالٍ للنكس. سندرس في هذا البحث أحد أنواع الأورام سنيّة المنشأ و هو الورم الكيسي السني المتقرن بشكليه نظير التقرن و عالي التقرن و علاقة جنس المريض و عمره بنمط هذا الورم. وتوصلنا إلى استنتاج وجود علاقة بين عمر و جنس المريض و نمط الورم حيث كانت الإصابة أعلى عند الذكور و توزعت بين العقدين الثالث و الرابع من العمر.